CLASSROOM-BASED STUDY ON TEACHING PRONUNCIATION THROUGH SONGS - Amonova Nafisa; Zulfiya Axmedova (TADQIQOTLAR, 2026)
Annotation: This article explores a classroom-based study on teaching English pronunciation through songs, focusing on the effectiveness of integrating music into language  learning  environments.  Pronunciation  is  a  crucial  component  of communicative competence; however, it often poses challenges for learners due to differences  in  phonological  systems,  stress  patterns,  rhythm,  and  intonation. Traditional teaching methods may not always provide sufficient exposure to natural speech, which makes alternative approaches necessary. The study aims to investigate how  songs  can  serve  as  an  effective  pedagogical  tool  to  improve  learners’ pronunciation  skills  in  an  engaging  and  meaningful  way.  Songs  offer  authentic language input, natural rhythm, repetition, and emotional engagement, which facilitate better retention and imitation of sounds. In this research, classroom activities such as listening  tasks,  singing  along,  phonetic  analysis,  and  repetition  exercises  were implemented  to  enhance  students’  pronunciation.  The  methodology  of  the  study  is based on a qualitative and quantitative approach, including classroom observations, pre-  and  post-tests,  and  student  feedback.  The  participants  were  English  language learners  at  an  intermediate  level.  The  results  demonstrate  that  the  use  of  songs significantly  improves  learners’  pronunciation  accuracy,  stress  placement,  and intonation patterns. Moreover, students showed increased motivation, confidence, and active participation during the lessons. The findings suggest that incorporating songs into pronunciation teaching not only makes the learning process more enjoyable but also creates a supportive environment for language acquisition. The study highlights the importance of selecting appropriate songs that match learners’ proficiency levels and linguistic needs. In conclusion, this research supports the integration of music-based  activities  as  an  effective  and  innovative  approach  in  teaching  English pronunciation in classroom settings.